1999
DOI: 10.1038/sj.bmt.1701942
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation in autologous bone marrow transplantation: cyclosporine and gamma-interferon trial

Abstract: Summary:From March 1994 to November 1994, 16 patients with high risk hematological malignancies were entered in a phase I clinical trial, designed to confirm the toxicity of cyclosporine and gamma interferon given to induce autologous graft-versus-host disease (GVHD) after autologous bone marrow transplantation (ABMT). This trial was based on the results in a rodent model, in which cyclosporine given after ABMT induces an autoimmune syndrome (autologous GVHD) identical to allogeneic GVHD. Further, this autolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Vogelsang et al 24 investigated the effect of marrow purging on auto-GVHD. Sixteen high-risk hematologic malignancy patients were conditioned with either Bu-Cy or Cy-TBI followed by infusion of 4-HC-purged bone marrow and then were given CsA 1 mg/kg/day as well as IFN-g 0.025 mg/m 2 every other day for 10 doses after early engraftment.…”
Section: Csa Plus Ifn-gmentioning
confidence: 99%
See 2 more Smart Citations
“…Vogelsang et al 24 investigated the effect of marrow purging on auto-GVHD. Sixteen high-risk hematologic malignancy patients were conditioned with either Bu-Cy or Cy-TBI followed by infusion of 4-HC-purged bone marrow and then were given CsA 1 mg/kg/day as well as IFN-g 0.025 mg/m 2 every other day for 10 doses after early engraftment.…”
Section: Csa Plus Ifn-gmentioning
confidence: 99%
“…10,14,19,21,22,24,26 Auto-GVHD generally appears within the first several weeks after auto-HCT, typically manifesting as a localized or more generalized erythematous maculopapular rash involving the face, trunk, extremities, palms and soles. The histopathologic appearance is inseparable from classic acute GVHD and rarely is greater than grade II in appearance.…”
Section: Incidence and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Several studies, both preclinical and clinical, have demonstrated that a syndrome similar to GVHD can in fact be induced in the autologous setting by using immunomodulation. [9][10][11][12][13][14][15][16][17][18] Based on this work, we tested the effect of two methods of immunotherapy following HDC with SCS in high-risk primary breast cancer. We hypothesized that the addition of immunomodulation would improve DFS when compared with historical controls.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Several clinical trials in patients with hematologic malignancies suggest that the induction of autologous GVHD can reduce relapse rate. [12][13][14][15] Disease-free survival among lymphoma patients who develop autologous GVHD is higher than in those who do not develop this autoaggression syndrome. 14,15 Autologous GVHD can be induced in 70-80% of autologous bone marrow (BM) recipients by administration of CsA in the early post autologous SCT period.…”
mentioning
confidence: 99%